Educational intervention on delirium assessment using confusion assessment method‐ICU (CAM‐ICU) in a general intensive care unit. Issue 21 (30th July 2018) - Ramoo, Vimala; Abu, Harlinna; Rai, Vineya; Surat Singh, Surindar Kaur; Baharudin, Ayuni Asma'; Danaee, Mahmoud; Thinagaran, Raveena Rajalachimi R
Abstract : Aims and Objectives: To assess intensive care unit nurses' knowledge of intensive care unit delirium and delirium assessment before and after an educational intervention. In addition, nurses' perception on the usefulness of a delirium assessment tool and barriers against delirium assessment were assessed as secondary objectives. Background: Early identification of delirium in intensive care units is crucial for patient care. Hence, nurses require adequate knowledge to enable appropriate evaluation of delirium using standardised practice and assessment tools. Design: This study, performed in Malaysia, used a single‐group pretest–posttest study design to assess the effect of educational interventions and hands‐on practices on nurses' knowledge of intensive care unit delirium and delirium assessment. Methods: Sixty‐one nurses participated in educational intervention sessions, including classroom learning, demonstrations and hands‐on practices on the Confusion Assessment Method‐Intensive Care Unit. Data were collected using self‐administered questionnaires for the pre‐ and postintervention assessments. Analysis to determine the effect of the educational intervention consisted of the repeated‐measures analysis of covariance. Results: There were significant differences in the knowledge scores pre‐ and postintervention, after controlling for demographic characteristics. The two most common perceived barriers to the adoption of the intensive care unit delirium assessment tool were "physicians did not use nurses' delirium assessment in decision‐making" and "difficult to interpret delirium in intubated patients". Conclusions: Educational intervention and hands‐on practices increased nurses' knowledge of delirium assessment. Teaching and interprofessional involvements are essential for a successful implementation of intensive care unit delirium assessment practice. Relevance to Clinical Practice: This study supports existing evidences, indicating that education and training could increase nurses' knowledge of delirium and delirium assessment. Improving nurses' knowledge could potentially lead to better delirium management practice and improve ICU patient care. Thus, continuous efforts to improve and sustain nurses' knowledge become relevant in ICU settings.